Athletic identity and sport commitment in athletes after anterior cruciate ligament reconstruction who have returned to sports at their pre-injury level of competition - Ohji, S.; Aizawa, J.; Hirohata, K.; Mitomo, S.; Ohmi, T.; Jinno, T.; Koga, H.; Yagishita, K. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background: This study aimed to determine the relationships between athletic identity and sport commitment and return to sports (RTS) status in athletes after anterior cruciate ligament reconstruction (ACLR). Methods: Thirty-nine participants post-ACLR (8-24 months) were included in this cross-sectional study. Measures included the athletic identity measurement scale and sport commitment scale. In addition, we measured kinesiophobia and psychological readiness using the Tampa Scale for Kinesiophobia and ACL-Return to sport after injury scale. The subjects were categorized into Yes-RTS or No-RTS based on two questions to determine whether they were returning to sport at the same level of competition as before the injury. A Chi-squared test, Fisher`s exact test, unpaired t-test, and Mann-Whitney`s U test were used to analyze the data. Results: The Yes-RTS group had significantly higher scores on the athletic identity measurement scale (P = 0.023, effect size [ES] = - 0.36), sport commitment scale (P = 0.027, ES = - 0.35), and ACL-Return to sport after injury scale (P = 0.002, ES = - 0.50) and significantly lower Tampa Scale for Kinesiophobia scores (P = 0.014, ES = - 0.39) compared to the No-RTS group. Conclusion: Athletes who returned to sports at the same level of competition as before the injury had higher athletic identity and sport commitment and lower kinesiophobia compared to those who did not return to sports at the same level of competition. These self-beliefs regarding sport may play an important role in post-ACLR athletes` RTS.